Analysis of Different Stripe Connectors for a Gabion Wall based on Woven Waste Tire Stripes - Arwan Apriyono; Sumiyanto Sumiyanto; Yanto Yanto; Sachrul Iswahyudi; Rino Wahyu Pamungkas (Institute of Research and Community Outreach - Petra Christian University, 2019)
In this research, woven waste tire stripes are proposed as an alternative material to wire mesh to make a gabion wall. The performance of the waste tire stripe-based gabion wall is highly dependent on the strength of its stripe, where the stripe connector plays an important role. This research aims to inspect the behavior of different stripe connectors for the gabion wall. To achieve this, a physical model was built and employed to test the strength of the gabion wall. Various stripe connectors are used; adhesive rubber glue, one inch nail, and two mm wire. The strength capacity of the models was determined from the maximum stress before failure. The strength capacities of the models are 83.197, 59.426 and 62.397 kPa for the wire, nail, and glue connector, respectively. Hence, it can be inferred that the wire connector is the strongest of the three connectors.